Effect of citric acid, tetracycline, and doxycycline on instrumented periodontally involved root surfaces: A SEM study - Gurparkash Singh Chahal; Kamalpreet Chhina; Vipin Chhabra; Rakhi Bhatnagar; Amna Chahal (Wolters Kluwer Medknow Publications, 2014)
Background: A surface smear layer consisting of organic and inorganic material is formed on the root surface following mechanical instrumentation and may inhibit the formation of new connective tissue attachment to the root surface. Modification of the tooth surface by root conditioning has resulted in improved connective tissue attachment and has advanced the goal of reconstructive periodontal treatment. Aim: The aim of this study was to compare the effects of citric acid, tetracycline, and doxycycline on the instrumented periodontally involved root surfaces in vitro using a scanning electron microscope. Settings and Design: A total of 45 dentin samples obtained from 15 extracted, scaled, and root planed teeth were divided into three groups. Materials and Methods: The root conditioning agents were applied with cotton pellets using the "Passive burnishing technique" for 5 minutes. The samples were then examined by the scanning electron microscope. Statistical Analysis Used: The statistical analysis was carried out using Statistical Package for Social Sciences (SPSS Inc., Chicago, IL, version 15.0 for Windows). For all quantitative variables means and standard deviations were calculated and compared. For more than two groups ANOVA was applied. For multiple comparisons post hoc tests with Bonferroni correction was used. Results: Upon statistical analysis the root conditioning agents used in this study were found to be effective in removing the smear layer, uncovering and widening the dentin tubules and unmasking the dentin collagen matrix. Conclusion: Tetracycline HCl was found to be the best root conditioner among the three agents used.